2011
DOI: 10.1093/infdis/jir723
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Immunogenicity of Inactivated Poliovirus Vaccine Made From Sabin Strains: A Phase II, Randomized, Positive-Controlled Trial

Abstract: NCT01056705.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 8 publications
2
46
0
Order By: Relevance
“…In a comparison study among Chinese population, the GMT after vaccinated by cIPV was 386 (297-502), while the GMT after vaccine with tOPV was 3315 (2703-4064). 24 Compared with I-I-B, I-B-B possessed a significantly higher PV1 reciprocal titer, while the PV3 reciprocal antibody titer in I-I-B was higher than in the I-B-B group. In the context of the final stage of polio eradication, PV2 immunity is of concern as well.…”
Section: Discussionmentioning
confidence: 86%
“…In a comparison study among Chinese population, the GMT after vaccinated by cIPV was 386 (297-502), while the GMT after vaccine with tOPV was 3315 (2703-4064). 24 Compared with I-I-B, I-B-B possessed a significantly higher PV1 reciprocal titer, while the PV3 reciprocal antibody titer in I-I-B was higher than in the I-B-B group. In the context of the final stage of polio eradication, PV2 immunity is of concern as well.…”
Section: Discussionmentioning
confidence: 86%
“…Recently, the phase II clinical trial of sIPV was conducted in China [15]. It was reported that the appropriate concentrations of sIPV were 15 DU, 32 DU, and 45 DU for types 1, 2, and 3, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…To mention one, clinical studies of IPV-containing vaccines have been conducted by subcutaneous administration as the standard method in Japan, and accordingly, the vaccines are subcutaneously administered by routine immunization. However, clinical studies of sIPV in other counties were conducted by intramuscular injection [80][81][82][83]. It is difficult to compare the safety and efficiency among different sIPV-containing vaccines in Japan and other countries because of the difference in the immunization routes of sIPV.…”
Section: "Vaccine Gap" In Japanmentioning
confidence: 99%
“…sIPV would be one of the most attractive and readily available options to be able to manufacture IPV at safer production facilities in middle-and low-income countries. At present, in addition to the three DTaP-sIPV manufacturers in Japan (Kaketsuken, Biken, and Takeda), sIPV has been independently developed by two other institutes, Intravacc (formerly part of the National Institute for Public Health and the Environment and Netherlands Vaccine Institute) and the Chinese Academy of Medical Sciences in Kunming, China (Kunming Institute), and both of which have started preclinical and clinical studies on sIPV [81][82][83][95][96][97][98][99][100] (Table 3).…”
Section: International Standardization Of Sipvmentioning
confidence: 99%
See 1 more Smart Citation